IMPLEMENTASI PASAL 2 PERATURAN PEMERINTAH NOMOR 7 TAHUN 2018 TENTANG PEMBERIAN KOMPENSASI TERHADAP ANAK SEBAGAI KORBAN TINDAK PIDANA PERDAGANGAN ORANG DI WILAYAH HUKUM KABUPATEN BENGKALIS - Pika wahyu pratama; Mukhlis R; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The issue of human trafficking has recently appeared to be a much debated problem both at the regional and global levels and is said to be a form of slavery today. Government Regulation Number 7 of 2018 concerning Providing Compensation, Restitution and Assistance to Victim Witnesses was signed with the consideration of providing protection to victim witnesses. This research was conducted in Bengkalis Regency. The sampling method was purposive sampling method, so the number of samples was 6 people. Data collection techniques by interview, observation and literature review. Data analysis using qualitative analysis. Based on the results of research, The implementation of Article 2 of the Government Number 7 of 2018 concerning the Provision of Compensation tochildren as victims of criminal acts of trafficking in persons in the Bengkalis Regency jurisdiction has not been implemented properly, there are weaknesses in the compensation arrangement, so that it is not fully oriented to the protection of victims of criminal acts. Constraint factors that hinder the implementation of compensation in cases of criminal acts of trafficking in persons are the role of law enforcers who do not pay attention to the rights of victims as a result of criminal acts of trafficking in persons, legal factors, namely overlapping laws and regulations governing the provision of compensation, the victim's low legal awareness of rights and mechanisms to obtain compensation, lack of ability and willingness of the defendant to pay compensation. Efforts to overcome obstacles to the implementation of Article 2 of the Government Number 7 of 2018 concerning the Provision of Compensation to children as victims of the crime of trafficking in persons is to increase the role of law enforcement when handling cases, the application for compensation should be carried out since the victim reports the case he experienced to the local Indonesian National Police. Keywords: Compensation, Victims, Trafficking in Persons